THE DEVELOPMENT OF FIELD LINGUISTICS AS A NECESSARY "NEED" - Avliyokulova Lola Bebutovna (Journals Park Publishing, 2024)
In order for the communication between a specialist and a non-specialist to have a positive result, there is a need not only to inform both sides about linguistics, but also to promote the language within various professions and fields. As this process is effective with the mutual understanding,comprehending of the two sides and the successful organization of the communication. In this article it is written about the demand of the time about developing linguistics which is considered a necessary "requirement" of today. The ideas that we would like to clarify in the article are considered as examples of a number of areas such as computer linguistics, sociolinguistics, psycholinguistics, numerology, medical linguistics, which arose at the intersection of two disciplines.
Keywords: : human, consumer, interdisciplinary integration, linguistics of a sector, computer linguistics, sociolinguistics, psycholinguistics, medical linguistics, numerology, number and numerals, professional speech culture, electronic dictionaries.